Effect of feeding Tephrosia bracteolate on the bioavailability of macro minerals in goat - Ogungbesan, AM; Adeleke, GA; Fasina, OE; Fajemisin, AN (Bangladesh Journal of Animal Science, 2021)
Sixteen West African Dwarf Goats (8 bucks and 8 does) were balanced for age, sex and weight (average of 5.79±0.60 kg), to evaluate the effect of Tephrosia bracteolata (Tb) on macro mineral utilization. To examine the effect of Tephrosia bracteolata (Tb), different levels of Tb were used (Tb20, Tb40, Tb60 and Tb80). Ca absorbed (gm) ranged from 0.64 (Tb20) to 1.57 (Tb80) and Ca retention was from 0.62 (Tb20) to 1.56 (Tb80) which was partially linear. In both absorption and retention of Ca, Tb20 and Tb80 found the lowest (P<0.05) and the highest (P<0.05) value respectively. Like Ca, P also followed the same trend in case of retention and absorption as well. Concerning Mg, the lowest (0.41, 0.40) and the highest (0.67, 0.65) absorbed and retained value (g/day) was observed in Tb 20 and Tb 80 respectively. Tb80 showed significantly higher Na absorption than Tb20. In case of Na retention, Tb80 showed the highest (P<0.05) retention than other groups. In K absorption (g/day), increasing trends (P<0.05) were observed from Tb20 (0.44) to Tb80 (1.25). In case of retention, Tb80 found the highest (P<0.05) K retention than other groups. These positive balances of minerals result linearly appreciating with the increase of T. bracteolata in the diets which might be due to leguminous properties in T. bracteolata. T. bracteolata can be used as a roughage source for goats without any remarkable adverse or, side or ill effects which affect the well-being of animals feeding. Bang. J. Anim. Sci. 2020. 49 (2): 119-127